Informed Trade of Earnings Announcements - XIE, CHLOE (Journal of Accounting Research, 2025)
ABSTRACT This paper examines how market participants trade on private information about firm fundamentals using the largest known case of informed trade of earnings announcements. From 2011 to 2015, a cartel of sophisticated traders illegally obtained early access to and traded on over 1,000 firm earnings announcements. Using this setting, I identify the information in earnings announcements that these market participants found most price relevant. The informed traders preferred announcements with larger earnings and sales surprises relative to forecasts, quantitative managerial guidance, and more extreme news sentiment. Despite their perfect foresight, the traders performed, perhaps surprisingly, poorly relative to hypothetical trading strategies based on comparable foresight. Frictions that limited their performance include price impact, risk aversion, and information processing costs. The trading performance of these informed traders implies that information about firm fundamentals explains little of the cross‐sectional variation in earnings announcement returns, even for sophisticated market participants.